(untitled) (Global Journal of Human-Social Science, 2015)
The main purpose of this study was to assess the problems in the teaching and learning of physics in the secondary and post-secondary (preparatory) schools of Wolaita and Dawuro zones. The study explored problems in the teaching and learning of physics from the following perspectives: problems related to school facilities, teachers, students, plasma instruction and the extent to which the school is conducive for practical activities. The research methodology employed in the study was a descriptive survey. Purposive, stratified and simple random sampling techniques were used to select the data sources of the study. Educational administrators (principals and vice principals), physics teachers, students, and supervisors at zonal and woreda levels were the subject of the study. Questionnaire and interview were the major data gathering instruments used for this study. Besides, some document analysis and personal observation were made to get additional evidences to the study. Numbers, percentage, mean values, grand mean and mean rank were the statistical tools used to analyze the data obtained from the subjects.